2016
DOI: 10.1007/s13365-016-0424-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 transgenic rats display mitochondrial abnormalities consistent with abnormal energy generation and distribution

Abstract: With the advent of the combination antiretroviral therapy era (cART), the development of AIDS has been largely limited in the United States. Unfortunately, despite the development of efficacious treatments, HIV-1 associated neurocognitive disorders (HAND) can still develop and as many HIV-1 positive individuals age, the prevalence of HAND is likely to rise because HAND manifests in the brain with very low levels of virus. However, the mechanism producing this viral disorder is still debated. Interestingly, HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…The effect of Tat upon ATP production has conflicting data (Perry et al 2005; Tiede et al 2011; Villeneuve et al 2016), with indications of both increases and decreases in ATP production, in all instances preceding cell death. Nevertheless, the ability of Tat to cause a drastic inhibition of ATP synthase (Lecoeur et al 2012; Norman et al 2007) points to a disruption of mitochondrial function.…”
Section: Viral Proteins and Mitochondriamentioning
confidence: 99%
“…The effect of Tat upon ATP production has conflicting data (Perry et al 2005; Tiede et al 2011; Villeneuve et al 2016), with indications of both increases and decreases in ATP production, in all instances preceding cell death. Nevertheless, the ability of Tat to cause a drastic inhibition of ATP synthase (Lecoeur et al 2012; Norman et al 2007) points to a disruption of mitochondrial function.…”
Section: Viral Proteins and Mitochondriamentioning
confidence: 99%
“…HIV proteins, such as transactivator of transcription (Tat), glycoprotein (gp) 120, viral protein (VP) R, and negative factor (Nef ) have been linked to immune activation, oxidative stress, altered mitochondrial transport, altered autophagic flux, induction of apoptosis, Ca 2+ signaling, and neurotoxicity (Bansal et al, 2000;Dinkins, Arko-Mensah, & Deretic, 2010;Nath, Conant, Chen, Scott, & Major, 1999;Nath, Padua, & Geiger, 1995;Piller, Jans, Gage, & Jans, 1998;Rozzi, Avdoshina, Fields, & Mocchetti, 2018;Sawaya, Khalili, Mercer, Denisova, & Amini, 1998;Teodorof-Diedrich & Spector, 2018;Thangaraj et al, 2018;Valcour & Shiramizu, 2004). The involvement of HIV proteins in mitochondrial dysfunction in the brain was highlighted in a study that found alterations in the electron transport chain (ETC), glycolytic pathways, mitochondrial trafficking proteins and proteins crucial to various energy pathways in a rat model for HIV-induced neurotoxicity (Villeneuve et al, 2016).…”
Section: Hiv Proteins and Mitochondrial Dysfunction In The Cnsmentioning
confidence: 99%
“…Later studies found alterations to mitochondrial related markers in the brains of HIV+ patients on cART, although the mechanisms of ART-induced neurotoxicity are not completely understood and also likely depend on genetic and environmental factors. To study the contribution of HIV and HIV proteins to HAND, rodent models were developed that expressed HIV proteins in the brain (Kim et al, 2003;Mucke, Masliah, Rockenstein, & Toggas, 1993;Villeneuve et al, 2016). Others have developed "humanized" mice that allow for HIV-infection to be recapitulated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of HIV-1 proteins, the mitochondria face a higher energy demand, will consume more oxygen, and show a higher capacity to produce ATP. These mechanisms are usually observed when there is cellular damage leading to ROS production [178].…”
Section: Advances In Hiv and Aids Control 12mentioning
confidence: 99%